Development and characterization of the electrospun melittin-loaded chitosan nanofibers for treatment of acne vulgaris in animal model. (28th June 2022) - Rahnama, Shahrbanoo; Movaffagh, Jebrail; Shahroodi, Azadeh; Jirofti, Nafiseh; Fazly Bazzaz, Bibi Sedigheh; Beyraghdari, Monir; Hashemi, Maryam; Kalalinia, Fatemeh
Acne is an inflammatory disease of the sebaceous glands. Melittin (Mel) is one of the principal toxic components of bee venom that can cause antibacterial and anti-inflammatory effects. Chitosan is a biodegradable polysaccharide has anti-inflammatory, antimicrobial, and regenerative properties. In this study, chitosan (Ch)/Mel 0.001 and 0.003% nanofibers were fabricated for topical treatment of acne vulgaris. Physicochemical properties of Ch/Mel were evaluated using FTIR and FESEM. Furthermore, encapsulation efficiency, tensile strength, water absorption capacity, enzymatic activity, drug release, antimicrobial, and cell cytotoxicity were assayed. Animal models were exerted to study the impact of Ch/Mel nanofibers on the treatment of Propionibacterium acnes . The FESEM results showed that nanofibers were successfully prepared in nano-scale fiber diameter. The FTIR confirmed the presence of Mel in structures. The addition of melittin to the polymer solution reduced electrical conductivity, induced viscosity and tensile strength of the fibers, and decreased the percentage of the swelling. The Mel loading into Ch/Mel 0.003% was reported at 86.74±1%. This Mel releasing process (89.65%) of Ch/Mel 0.003% was slowly completed during 72 h. The Mel retained its hemolytic activity after being loaded into the polymer structure. The drug toxicity study displayed the lack of any significant toxicity from Ch/Mel nanofibers on normal Human Dermal Fibroblasts (HDF). The Ch/Mel 0.003% achieved the highest growth inhibition in P. acnes in vitro and animal studies, this group showed the greatest reduction in inflammation and redness. The Ch/Mel 0.003% structure is proposed as a suitable topical drug delivery system for treating acne vulgaris.